Quantitative swept-source optical coherence tomography angiography (SS-OCTA) analysis of macular microvascular alterations in Bietti crystalline dystrophy - Shiyi Yin; Jinyuan Wang; Haihan Zhang; Xuan Yang; Jingting Luo; Wenbin Wei (Photodiagnosis and Photodynamic Therapy)
Purpose: Bietti crystalline dystrophy (BCD) is a rare retinal dystrophy characterized by progressive visual impairment. This study aimed to evaluate changes in retinal and choroidal vessels and blood flow in BCD patients using swept-source optical coherence tomography angiography (SS-OCTA) and to investigate potential parameters associated with visual function. Methods: This cross-sectional study included 166 eyes from 86 clinically diagnosed BCD patients, classified into three disease stages based on Yuzawa's classification. OCTA imaging (VG200S; SVision Imaging, Henan, China) covered a 12 mm × 12 mm area of the macula, measuring thickness, vessel density (VD), perfusion area (PA), choroidal vascularity index (CVI), choroidal vascularity volume (CVV), and foveal avascular zone (FAZ) metrics. Associations between OCTA parameters and visual function metrics, including best-corrected visual acuity (BCVA), mean deviation (MD) and visual field index (VFI) of the Humphrey visual field test, were analyzed. Results: By stage 3, 92 % of eyes exhibited an undetectable ellipsoid zone (EZ). From stage 1 to stage 2, VD in all retinal layers decreased significantly (P < 0.05), whereas differences between stages 2 and 3 were not statistically significant (P > 0.05). The FAZ area and perimeter showed no significant difference across the three stages (P > 0.05). Choroidal parameters, including PA, CVI, and CVV, progressively decreased across all stages (P < 0.001). Multivariate regression analysis revealed that SVC-VD (P < 0.001), SVC-PA (P < 0.001) and choroid-PA (P = 0.030) were significantly associated with BCVA, while DVC-VD (P = 0.014), outer retinal thickness (P = 0.011), and CVI (P = 0.004) were significantly associated with visual field damage. Conclusions: SS-OCTA effectively quantifies the progressive microvascular changes in the retina and choroid associated with BCD. Retinal vascular alterations are prominent in the early stages of the disease, whereas choroidal damage persists throughout its progression. OCTA parameters of the retina and choroid demonstrate varying degrees of correlation with visual function, underscoring their potential as biomarkers for monitoring disease progression and evaluating therapeutic efficacy.